Коливальні стани кластерів, які моделюють адсорбційні комплекси кисню на грані Si(100) - Terebinska, M. I.; Filonenko, O. V.; Lobanov, V. V. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2014)
Vibrational states (frequencies and forms of vibrations) of O2 molecules adsorption complexes were calculated due to density functional theory method (B3LYP, 6-31G **). These complexes recreate the conversion of molecular oxygen adsorbed complexes containing siloxane bonds. Frequencies which were experimentally found are corresponding with the oxygen-containing structures.